Pengaruh Financial Distress dan Good Corporate Governance terhadap Manajemen Laba - Eka Sulistia Minarti; Suwarno Suwarno (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine the effect of financial distress and good corporate governance on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (BEI). The sampling method used was a purposive sampling method based on predetermined criteria. The samples used in this research were 60 samples from manufacturing companies period 2022. The results of this research show that the variables financial distress, institutional ownership, and audit committee have no effect on earnings management. Meanwhile, managerial ownership has a negative effect on earnings management.